Students' attitudes towards the use of mobile technologies in e-Evaluation - Al-Emran, Mostafa; Salloum, Said A. (International Association of Online Engineering, 2017)
Mobile learning (M-learning) is a new wave in the era of educational technology that provides informal, personal, voluntary and situated learning opportunities for both learners and educators. Mobile-based assessment is one of the emerging technologies that attract many scholars to investigate its effectiveness due to the wide spectrum of its features like portability, interactivity, flexibility, and ubiquity. Based on the surveyed literature, we noticed that there is a lack of studying the students' attitudes towards the utilization of mobile technologies in the context of e-Evaluation. The present study attempts to investigate the students' attitudes towards the utilization of mobile technologies in the e-Evaluation system of instructors. The data was collected through a questionnaire survey from Al Buraimi University College (BUC) in Oman. The total number of participants is 354 students. Findings indicated that 99% of the students own a mobile phone or tablet. Moreover, results indicated a statistically significant difference among the students’ attitudes in terms of their gender where the differences were in favor of male students. In contrast, results revealed no statistically significant differences among the students’ attitudes in terms of their age, degree, and department. Furthermore, other implications and future work are also reported in the study.